Radiation-induced alterations in immunogenicity of a murine pancreatic ductal adenocarcinoma cell line - Schröter, Philipp; Hartmann, Laura; Osen, Wolfram; Baumann, Daniel; Offringa, Rienk; Eisel, David; Debus, Jürgen; Eichmüller, Stefan B.; Rieken, Stefan (Scientific reports, 2020)
Pancreatic ductal adenocarcinoma (PDA) is highlighted by resistance to radiotherapy with the possible exception of hypofractionated irradiation. As single photon doses were reported to increase immunogenicity, we investigated dose-dependent irradiation effects on clonogenic survival, expression of immunologically relevant cell surface molecules and susceptibility to cytotoxic T cell (CTL) mediated killing using a murine PDA cell line. Clonogenicity decreased in a dose-responsive manner showing enhanced radioresistance at single photon doses below 5 Gy. Cell cycle analysis revealed a predominant G2/M arrest, being most pronounced 12 h after irradiation. Polyploidy increased in a dose- and time-dependent manner reaching a maximum frequency 60 h following irradiation with 10 Gy. Irradiation increased surface expression of MHC class I molecules and of immunological checkpoint molecules PDL-1 and CD73, especially at doses ≥ 5 Gy, but not of MHC class II molecules and CXCR4 receptors. Cytotoxicity assays revealed increased CTL lysis of PDA cells at doses ≥ 5 Gy. For the PDA cell line investigated, our data show for the first time that single photon doses ≥ 5 Gy effectively inhibit colony formation and induce a G2/M cell cycle arrest. Furthermore, expression levels of immunomodulatory cell surface molecules became altered possibly enhancing the susceptibility of tumour cells to CTL lysis.
Gesehen am 25.09.2020